Corrosion‐resistant coating development with potential application in equipment of low‐temperature waste heat recovery. (5th October 2017) - Zhuang, Quan; Geddis, Phil; Clements, Bruce; Ko, Vivien
Abstract: In order to improve corrosion resistance of a condensing heat exchanger, a fluoropolymer, perfluoroalkoxy alkane (PFA), fine powder in 30 wt% aqueous slurry was coated on metal coupons and a coating of high quality finish was obtained. The coating was characterized by microscopy and thickness measurements. The thickness of the coating can be controlled by the number of layers used for the application of wet spray. Hot acid bath corrosion tests showed that the coated coupon possesses the highest adhesion strength and excellent corrosion resistance (1.8–6.7 × 10 −3 mm/year), comparable to super alloys such as Inconel (1.1–26.2 × 10 −3 mm/year) and Hastelloy (0.3–19.8 × 10 −3 mm/year). A heat transfer coefficient analysis showed that across a heat transfer metal tube coated with PFA, the heat transfer resistance of the gas side film is one order of magnitude larger than the resistance from the coated layer. The developed coating could provide an alternative material solution for condensing heat exchangers used in low‐grade waste heat recovery.